Sustainable supply chain management: issues & challenges identification - Arwa, Mukhtar; Awanis, Romli; Abdulgabber, Mansoor Abdullateef (Universiti Malaysia Pahang, 2018)
The aim of this paper is shedding light on the issues and challenges of sustainable supply chain management (SSCM) adoption in supply chain operations. Sustainability practices adoption has received an increasing attention over time. However, tackling SSCM challenges is dominant to assure optimal supply chain operations. Therefore, to detect the obstacles and challenges on SSCM, reviewing the extant literature is required. Following the manual search method in 17 journals result in 61 relevant studies in SSCM literature. The relevant studies extensively reviewed to highlight the critical trends in the sustainable responsibility challenge. And an illustration of the current sustainability challenges has been identified. The findings showed twenty-one dominant challenges in SSCM. The challenges identification provides useful insights for SSCM adoption. It is not only beneficial for decision–makers, supply chain stakeholders and practitioners, but also highlighting unexplored areas and offering additional research opportunities for researchers.